2013
DOI: 10.3390/ijms141122997
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Tight Junction Gene Expression by Calcium- and Vitamin D-Deficient Diet in the Duodenum of Calbindin-Null Mice

Abstract: Calcium absorption is regulated by both active (transcellular) and passive (paracellular) pathways. Although each pathway has been studied, correlations between the two pathways have not been well elucidated. In previous investigations, the critical transcellular proteins, calbindin-D9k (CaBP-9k) and -D28k (CaBP-28k), were shown to affect other transcellular pathways by buffering intracellular calcium concentrations. The rate of paracellular calcium transport in the duodenum is generally determined by the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…In vivo experiment also revealed downregulation of claudin-2 and -12 in the duodenum, ileum, and colon of the VDR knockout mice at both transcriptional and translational levels (Fujita et al, 2008). Similarly, Hwang et al (2013) showed downregulation of claudin-2 as well as claudin-15 mRNAs and proteins in the duodenum of calcium/vitamin D-deficient calbindin-D 9k knockout mice. On the other hand, high concentration of 1,25(OH) 2 D 3 conversely suppressed claudin-3 mRNA expression in the rat duodenum as determined by Affymetrix microarrays (Kutuzova & DeLuca, 2004).…”
Section: Charge-and Size-selective Properties Of Tight Junctionmentioning
confidence: 79%
See 2 more Smart Citations
“…In vivo experiment also revealed downregulation of claudin-2 and -12 in the duodenum, ileum, and colon of the VDR knockout mice at both transcriptional and translational levels (Fujita et al, 2008). Similarly, Hwang et al (2013) showed downregulation of claudin-2 as well as claudin-15 mRNAs and proteins in the duodenum of calcium/vitamin D-deficient calbindin-D 9k knockout mice. On the other hand, high concentration of 1,25(OH) 2 D 3 conversely suppressed claudin-3 mRNA expression in the rat duodenum as determined by Affymetrix microarrays (Kutuzova & DeLuca, 2004).…”
Section: Charge-and Size-selective Properties Of Tight Junctionmentioning
confidence: 79%
“…1,25(OH) 2 D 3 also modulates the expression of duodenal nonclaudin tight junction-related proteins, such as zonula occludens protein (ZO) and occludin (Hwang et al, 2013). Hwang et al (2013) found the expressions of occludin and ZO-1 transcripts to be downregulated in calbindin-D 9k knockout mice given calcium-and vitamin D-deficient diet, but not normal diet. Western blot and immunohistochemical analyses of ZO-1 in duodenum also showed similar trend as mRNA results.…”
Section: Charge-and Size-selective Properties Of Tight Junctionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our diet was low in calcium and vitamin D, both needed for tight junction physiology. In the calbindin-null mice, a calcium and vitamin D deficient diet resulted in down-regulation of tight junction genes (32). Tight junction protein expression is regulated through ERK1/2 and AKT signaling (33,34), both of which were clearly down-regulated in our WD mice.…”
Section: Discussionmentioning
confidence: 66%
“…40 Further, compensatory increases in Cldn2 and Cldn15 were observed in the duodenum of adult CaBP9k KO mice, suggesting the possibility of a cooperative interaction between the transcellular and paracellular calcium absorption pathways. 46 …”
Section: Paracellular Calcium Absorptionmentioning
confidence: 99%